Neoplasta Coquillett (Diptera: Empididae: Hemerodromiinae) from Brazil: new species and male description of N. fortiseta Smith - Câmara, Josenir T.; Rafael, José A. (Zootaxa, 2016)
Neoplasta Coquillett is distributed in the New World. The male of N. fortiseta Smith and five new species collected in the Brazilian states of Santa Catarina and São Paulo (N. lobata sp. nov., N. longicornis sp. nov., N. macdonaldi sp. nov., N. nigrithorax sp. nov., and N. spinulosa sp. nov.), are described and illustrated. A key to Brazilian species is provided.